Philosophical profiles : essays in a pragmatic mode - Bernstein, Richard J. (University of Pennsylvania Press, 1986)
Philosophical Profiles brings together ten important essays by Richard Berstein. Each focuses on the work of a thinker or group of thinkers at the center of contemporary developments in philosophy, including Hannah Arendt, John Dewey, Hans-Georg Gadamer, Jurgen Habermas, G.W.F. Hegel, Alasdair MacIntyre, Herbert Marcuse, and Richard Rorty.